ICMT supports BRAF V600E -driven tumor growth by membrane targeting of the CAAX protein INPP5E - Xijie Yang; Xi Qiao; Sarah Schmidt; Ella A. Eklund; Carolina Ebner-Walter; Emil Ivarsson; Michelle Ann Crespo; Nadieh Kersemakers; Jozefina J. Dzanan; Bjarni Thorisson; Christine Lundgren; Hooi Ching Lim; et al. (Proceedings of the National Academy of Sciences, 2026)
Isoprenylcysteine carboxyl methyltransferase (ICMT) catalyzes C-terminal methylation of prenylated CAAX proteins, a final processing step promoting membrane association and signaling. Although ICMT has been pursued to disrupt RAS membrane targeting, its role in BRAF V600E -driven cancers and critical substrates remains unclear. Here, genetic and pharmacologic (UCM-1336) ICMT inhibition suppressed proliferation and invasion in BRAF V600E -mutant melanoma cells and reduced tumor growth in xenografts and mice. ICMT knockdown inhibited proliferation of BRAF-inhibitor-resistant melanoma cells. We identify INPP5E as an ICMT-dependent substrate: ICMT inhibition reduced INPP5E methylation, displaced it from membranes, and increased PI(4,5)P 2 . Forced INPP5E membrane targeting partially rescued growth defects caused by ICMT inhibition. These findings implicate an ICMT-INPP5E-axis that supports BRAF V600E -driven tumor growth.